2018
DOI: 10.1002/btpr.2753
|View full text |Cite
|
Sign up to set email alerts
|

Combining chemical flocculation and bacterial co‐culture of Cupriavidus taiwanensis and Ureibacillus thermosphaericus to detoxify a hardwood hemicelluloses hydrolysate and enable acetone–butanol–ethanol fermentation leading to butanol

Abstract: Butanol, a fuel with better characteristics than ethanol, can be produced via acetone–butanol–ethanol (ABE) fermentation using lignocellulosic biomass as a carbon source. However, many inhibitors present in the hydrolysate limit the yield of the fermentation process. In this work, a detoxification technology combining flocculation and biodetoxification within a bacterial co‐culture composed of Ureibacillus thermosphaericus and Cupriavidus taiwanensis is presented for the first time. Co‐culture‐based strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Ureibacillus sp. is well known for its high efficiency in removing phenolic compounds, its production of a broad range of lignocellulolytic enzymes, including laccases, tyrosinase, peroxidases, catalases, and oxidases, and efficiently degrading furfural and 5-hydroxymethylfurfural with minor sugar consumption (< 5%) [ 24 ]. Pseudoxanthomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Ureibacillus sp. is well known for its high efficiency in removing phenolic compounds, its production of a broad range of lignocellulolytic enzymes, including laccases, tyrosinase, peroxidases, catalases, and oxidases, and efficiently degrading furfural and 5-hydroxymethylfurfural with minor sugar consumption (< 5%) [ 24 ]. Pseudoxanthomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the ECs investigated here all contain at least one aromatic ring, their biodegradation could be catalyzed by enzymes related to those involved in hydrocarbon biodegradation. Brevibacillus , Ureibacillus , and Corynebacterium strains aerobically degrade PAHs (Lee et al., 2018; Reddy et al., 2010; Theiri et al., 2019), and Desulfitobacterium and Proteiniphilum strains anaerobically degrade PAHs (Larsen et al., 2009; Tartakovsky et al., 1999). Although our experimental design sought to create aerobic conditions, the possibility that anaerobic micro‐niches were present (e.g., within aggregated cells) remains.…”
Section: Discussionmentioning
confidence: 99%
“…Yang (Yang et al, 2016) revealed that the relative abundances of the other predominant bacteria such as Brevibacillus, Ureibacillus and Pseudomonas were positively related to the fermentation duration, reaching the peak after 1 week of fermentation. Researches also demonstrated that Brevibacillus fermentation could produce glutamate (Momose & Takagi, 2014), Ureibacillus could decompose cellulose to butanol (Mariem et al, 2018), and most Pseudomonas could produce one kind or more kinds of protease, lipase, and lecithin enzymes (Dogan & Boor, 2003), thereby enhancing the flavor of the Douchi.…”
Section: Compare Bacterial Distribution Of Different Types Of Douchimentioning
confidence: 99%